Regional Stratigraphic Framework of Surficial Sediments and Bedrock Beneath Lake Ontario - Hutchinson, D.; Lewis, C.F.; Hund, G. (Géographie physique et Quaternaire, 1993)
ABSTRACTApproximately 2550 km of single-channel high-resolution seismic reflection profiles have been interpreted and calibrated with lithological and geochronological information from four representative piston cores and one grab sample to provide a regional stratigraphie framework for the subbottom deposits of Lake Ontario. Five units overlying Paleozoic bedrock were identified and mapped. These are classified as informal units and represent, from oldest to youngest: (A) subglacial till (?) deposited by the Port Huron ice at the end of the Wisconsin glaciation; (B) an ice-marginal (?) unit confined to the western part of the lake that was probably deposited during retreat of the Port Huron ice shortly after 13 ka; (C) a regionally extensive unit of laminated glacio-lacustrine clay that accumulated until about 11 ka; (D) a weakly laminated to more massive lake clay deposited during a period of reduced water supply and rising water levels after the drawdown of the high-level glacial lakes (Iroquois and successors); and (E) modern lake clay less than 10 m thick that began accumulating around 6-8 ka with the subsequent return of upper Great Lakes drainage through the Ontario basin. Seismic reflections also define the configuration of the bedrock surface and pre-glacial stream valleys incised in the bedrock surface. Several anomalous bottom and subbottom features in the surficial sediments are mapped, such as discontinuous and offset reflections, furrows, gas pockets, and areas of large subbottom relief. None of these features appear to be spatially correlative with the diffuse seismicity that characterizes the lake area or with deeper structures such as Paleozoic bedrock faults or crustal-penetrating faults in the Precambrian basement.